Evaluation of Gilsonite and Styrene-Butadiene-Styrene Composite Usage in Bitumen Modification on the Mechanical Properties of Hot Mix Asphalts - Yilmaz, Mehmet; Yamac, Ozge Erdogan (Asce-Amer Soc Civil Engineers, 2017)
This study is an investigation of the rheological properties of bituminous binders and the mechanical properties of hot mix asphalts (HMAs) when a combination of styrene-butadiene-styrene (SBS) and American Gilsonite (AG) is added to bitumen. In this work, HMAs were prepared with two binders containing a single additive (5% SBS and 18% AG) and three binders containing two different additives (4% SBS + 6% AG, 3% SBS + 10% AG, and 2% SBS + 13% AG), which have the same Superpave performance levels. Tests carried out on the mixes demonstrated that the most effective additives relative to Marshall stability, retained Marshall stability, and indirect tensile strength values were 18% AG and 3% SBS + 10% AG; the most effective additives relative to stiffness and fatigue life were 18% AG, 2% SBS + 13% AG, and 3% SBS + 10% AG; and the most effective additives against moisture-induced damage were 5% SBS, 2% SBS + 13% AG, and 3% SBS + 10% AG. A consideration of all of the study's findings indicate that the utilization of a combination of SBS and AG is provides more benefits than utilizations of SBS or AG alone. (C) 2017 American Society of Civil Engineers.
Keywords: Bitumen; Modification; Hot mix asphalt; Gilsonite; Styrene-butadiene-styrene